Case on How to Improve of Supply Chain Productivity - Siti Noraini, Abdul Malek (Penerbit UMP, 2017)
Efficient supply chain management is crucial for survival and success in a stormy world. “Supply chain management is about developing a process to respond to the different requirements of each customer. Customers are driving suppliers' practices. Being successful requires logistics effectiveness. Supply chain management should be an integral part of the company's drive and direction. Its represents the way to customer retention and growth, competitive advantage and profitability. Successful supply chains have top management approval and support”(inpressco.com).